Exploring Listening Proficiency Among University Students - Theresia Yolanda Nababan; Natalia Widya Pasca Tarigan; Wariyati Wariyati (Teaching English and Language Learning English Journal, 2025)
This study aims to analyze the listening skills of students at STIKES Columbia Asia Medan and identify the factors that influence their listening comprehension. Employing a descriptive qualitative method, data were collected through an IELTS-format listening test provided by the British Council and semi-structured interviews. The results showed that 45% of students achieved an “Excellent” level, 25% were categorized as “Very Good,” 10% as “Good,” and 20% as “Fair,” with no students falling into the “Failed” category. The qualitative findings revealed several key factors affecting listening performance, including limited vocabulary, difficulties in understanding foreign accents, lack of concentration, minimal exposure to authentic English, unfamiliarity with test formats, and psychological aspects such as anxiety. The study concludes that British Council listening materials can effectively support listening skill development, but they must be complemented by comprehensive teaching strategies and consistent practice.